Testing the boundaries of the green algal species Pediastrum alternans (Chlorophyceae) using conventional, geometric morphometric and phylogenetic methods. Issue 5 (1st September 2016) - Lenarczyk, Joanna; McManus, Hilary A.
Abstract: This article focuses on a detailed morphological and molecular analysis of the microscopic green alga Pediastrum alternans as it exhibits ambiguous morphology, questionable phylogenetic position and scattered distribution. The species, originally described from lakes close to the Baltic Sea in Denmark, was recently renamed Pseudopediastrum alternans based on rDNA sequencing of one culture from Namibia. In the present study, the African culture was morphologically and genetically compared with a culture identified as Ps. alternans from a coastal lake from northern Poland and a culture of Ps. boryanum var. longicorne from southern Poland. Conventional measurements, statistical and geometric morphometric analyses of the number of cells in coenobia, cell shape and size and wall ornamentation showed significant differences in the morphology of the three cultures. The analyses supported the phylogenetic distinction of the cultures based on rDNA and chloroplast DNA sequencing. Cultures of Pseudopediastrum alternans from Africa and Poland were not monophyletic. The African culture was moderately supported in a clade that could potentially represent a new species of Pseudopediastrum ; whereas, the Polish culture formed a distinct lineage that was sister to some Ps. boryanum strains. The third culture, identified as Ps. boryanum var. longicorne, was nested within Ps. boryanum, as expected based on its morphology. Additional morphological comparison between the cultures and the iconotype showed that the Polish culture fits the description of Ps. alternans ; whereas, the African one is so different from the iconotype that it cannot be called Ps. alternans . Analysis of plasticity of the Polish culture showed that its morphology is rather stable under varying nutrient and salinity conditions, and the culture cannot be misidentified as other Pseudopediastrum species.